Morphological and Morphmetric Studies on Embryo Development in Camphor Treated Pregnant Rats - Sabah A. Linjawi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Camphor has long been used in dead bodies wash in Saudi Arabia. Experiments were conducted to study the effect of camphor on SpragueDawley rats and embryos. Pregnant rats (n = 36) were divided into 4 groups (n = 9); 3 groups were given intraperitoneal injection by different doses of water camphor solution (5, 10 and 20 mg camphor/kg body weight); control group was given the same doses of distilled water. All groups were kept in constant room temperature (22o± 2oC), and in a 12 h light/12 h dark photoperiod. At the end of 1st, 2nd and the 3rd week of gestation, 3 animals from each group were anesthetized; their plasma and embryos were removed. The results obtained showed a significant increase in body weight of pregnant rats in week 1 of gestation for G2 (10 mg/kg), and in week 2 of gestation for G3 (20 mg/kg) compared to control. The hormonal analysis did not show significant differences with all used doses. However, a significant decrease in fetal body length and weight were recorded, increase in number of dead and incomplete growth embryos in G3 (20 mg/kg) were observed. The present study shows that camphor effects on rats embryos. Therefore, caution is recommended in its use, especially for pregnant women.